Systemic Sarcoidosis Unmasked by Cushing's Disease Surgical Treatment - Bongetta, Daniele (Case Rep Med, 2016)
Diseases responsive to glucocorticoids, like sarcoidosis, are rarely masked by Cushing's syndrome. An ACTH secreting pituitary adenoma is a possible cause of Cushing's syndrome and its resection can make a subclinical sarcoidosis clear. Only few cases of sarcoidosis following the treatment of hypercortisolism are reported in literature. We report a case of sarcoidosis after the resection of an ACTH secreting pituitary adenoma.